Protection and Guarantee of Human Dignity taking into Account the Practical Ideas of the “National System of School Coexistence”. Analysis with Students of San Pedro Claver Educational Institution of Chitaraque Municipality - Morales-Doza, María Paola (Universidad Pedagógica y Tecnológica de Colombia, 2016)
This paper is a reflection on the coexistence processes and the application  of legal instruments to protect the rights of children and adolescents in the school context, specifically the one developed by the National System of School Coexistence, created since the enactment of the law 1620 on March 13, 2013, to identify the elements that protect and guarantee the human dignity of students of IE San Pedro Claver school, in Chitaraque.